PERANAN PERILAKU SOSIAL PT. ARMADA MIX BANJARBARU SEBAGAI BENTUK PERTANGGUNGJAWABAN SOSIAL PERUSAHAAN TERHADAP LINGKUNGAN SEKITARNYA - yudi rahman (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Abstract The purpose of this study was to study the social role at PT. Banjarbaru Fleet Mix as a form of corporate social responsibility to the environment around the company that is carried out and carried out by the company so far can provide input on the basic concepts of social responsibility accounting which are carried out in accordance with the theory carried out. The method used is a description method that discusses the evaluations carried out by companies that are conceptualized in social responsibility carried out by Social Responsibility Measurement and Reporting. In conducting this research, the author uses the method of data collection by means of observation, interviews and documentation. From the research that has been done, the writer obtained from the research conducted by PT. Banjarbaru Fleet has conducted several activities which include companies for the community, contributing companies to the environment and contributing companies to human resources. and contributing companies to products and services. Financial Statements, Social Responsibility conceptualized through Descriptive, cost planning incurred and cost planning Benefits will make changes to the company in accordance with the concept of good accountability. Keywords: Role of social behavior, social responsibility and the surrounding environment